THE DYNAMIC OF POWER RELATIONS OVER BOMBANAS GOLD MINING IN SOUTEAST SULAWESI INDONESIA - Amri, Ulil (Sekolah Pascasarjana UGM, 2011)
In mid-2008 a new gold mining site was discovered in bombana Regency